Instructions
Write the equation in the standard form of ax^2 + bx + c = 0. For the example, write:
x^2 + 2x - 9 = 0.
Isolate the x^2 and x terms by subtracting the last term from both sides:
x^2 + 2x -9 -(-9) = -(-9) or
x^2 + 2x = 9
This equation remains equivalent; you have simply rearranged it.
Add a term to both sides equal to (b / 2)^2. In this example, b = 2, so (b / 2)^2 = 1. So you add 1 to both sides:
x^2 + 2x + 1 = 9 + 1
The square is now complete. x^2 + 2x + 1 on the left side is a perfect square, namely,
(x + 1)^2.
Rewrite the equation in terms of the perfect square:
(x + 1)^2 = 9 + 1
You can simplify this to:
(x + 1)^2 = 10
Solve the resulting equation algebraically. Take the square root of both sides:
x + 1 = +/- sqrt(10)
Where "sqrt(10)" means "the square root of 10." Remember, when you take the square root, the result is positive or negative. Subtracting 1 from both sides leaves x on the left side:
x = -1 +/- sqrt(10). The original equation, x^2 +2x -- 9 = 0 has two roots which result in zero, namely -1 + sqrt(10) and -1 -- sqrt(10).